2016
DOI: 10.1111/jfbc.12333
|View full text |Cite
|
Sign up to set email alerts
|

Black adzuki bean (Vigna angularis) extract exerts phenotypic effects on white adipose tissue and reverses liver steatosis in diet-induced obese mice

Abstract: The primary objective of this study was to examine the extent to which black adzuki bean (BAB) extract attenuates the development of high‐fat diet‐induced obesity in mice. Four‐week‐old C57BL/6J mice were fed one of the following diets for 12 weeks: control diet containing 10% of its energy as fat (CD); high‐fat diet, containing 60% of its energy as fat (HD); high‐fat diet mixed with 1% freeze‐dried BAB extract powder (BAB); or high‐fat diet mixed with 0.08% kaempferol (Kfr). Compared to the HD group, the BAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Similarly, black soybean powder decreased AST in the high cholesterol/fat diet-induced nonalcoholic fatty liver disease mice model [ 39 ]. The ethanol extracts from adzuki beans significantly decreased AST and ALT in high fat diet-induced obese mice [ 40 ]. In addition, adzuki bean water extracts reduced serum AST in a rat model that showed hepatotoxicity by acetaminophen [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, black soybean powder decreased AST in the high cholesterol/fat diet-induced nonalcoholic fatty liver disease mice model [ 39 ]. The ethanol extracts from adzuki beans significantly decreased AST and ALT in high fat diet-induced obese mice [ 40 ]. In addition, adzuki bean water extracts reduced serum AST in a rat model that showed hepatotoxicity by acetaminophen [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research studies involving the use of adzuki bean extract on animals also yielded uncertain outcomes regarding the effectiveness of adzuki bean extract in addressing obesity. Some studies reported positive results on the efficacy of adzuki bean supplementation in reducing obesity [ 38 , 39 , 48 , 52 , 55 ]. Lee et al [ 38 ] found that providing mice with 200 mg adzuki bean extract/kg BW/day significantly decreased the fat mass increased by a 12-week consumption of a high-fat diet ( p < 0.05).…”
Section: Role Of Adzuki Bean Supplementation In Managing Obesity Outc...mentioning
confidence: 99%
“…The sample types, experimental models, and major results are listed in Table 1. The samples used in these studies were mostly prepared by whole seeds (Choi et al., 2020; Ha et al., 2021; Kim et al., 2017, 2019; Kitano‐Okada et al., 2019; Lee et al., 2019; Yook et al., 2017; Zhu et al., 2019). On the other hand, few studies focused on the bioactivity of adzuki bean constituents, such as proteins and peptides (Ashraf et al., 2020; Chen et al., 2017; Senpuku et al., 2019).…”
Section: Health Benefits Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…Decreases in body and liver weight gains and serum and liver lipid levels (e.g., cholesterol and triglyceride triacylglycerols) in different murine models were observed after the ingestion of adzuki bean extracts (Choi et al., 2020; Kim et al., 2017), pastes (Han, Oshahi, et al., 2020), purified flavonoids and saponins (Liu, Zheng, et al., 2017), and isolated 7S globulins (Ferreira et al., 2015), usually accompanied with increased excretion of fecal lipid and acidic sterol. These effects were related to the down‐regulation of lipogenic and lipolysis‐related transcriptional factors and the up‐regulation of fatty acid oxidation‐related transcriptional factors (Kim et al., 2017; Lee et al., 2019). Furthermore, reduced food intake was observed in different murine models, which might be attributed to the regulation of the hypothalamic neuropeptide expression (Kim et al., 2015).…”
Section: Health Benefits Of Adzuki Bean and Its Componentsmentioning
confidence: 99%